Efficacy of Using Non-tunneled Dialysis Catheters During Arteriovenous Fistula till its Maturation: A Retrospective Study - Kazemzadeh, Gholam Hossein; Bazrafshan, Maziar; Kamyar, Mohammad Mahdi; Hashemi Fard, Adeleh (Urology Journal, 2019)
Purpose: Due to high prevalence of diabetes mellitus and subsequent nephropathy, the need for access to start and continue dialysis has been increased. In this study, we aim to study the efficacy and complications of non-tunneled catheters (NTC) till fistula maturation because of being easy and cheap implementation as well as similar complications compared to tunneled catheters (TC). Materials and Methods: In this retrospective observational study, 247 patients with first-time AVF creation referred to Vascular Surgery Centre of Mashhad University of Medical Sciences, Iran, were recruited since March 2016 to December 2017. Only 153 patients who have completed the study, and were monitored every two weeks in case of un-maturation along with the status of temporary catheters. Results: Mean age of patients was 49.9 ± 7.74 years, and 75 (49%) were females, which was comparable with literature. Preference of NTC implementation was at right jugular because of the easy access to central vein and less chance of complications. Catheter location was at right internal jugular in 61.4% of the patients. Out of 24 femoral cases, 18 was done at femoral. AVF location was done at left/right cubital in most cases (52.3%). The rate of infection was 15.0%, which was less than NTC’s infections reported in the literature. Conclusion: Use of non-tunneled catheter in the form of outpatient in the period of AVF maturation time is recommended due to similar complication rate.